Transmission investment in the Peruvian electricity market: Theory and applications - Erix Ruiz; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This research presents an application of the Hogan, Rosellón and Vogelsang (2010) (HRV) mechanism to promote electricity transmission network expansion in the Peruvian electricity transmission system known as SEIN (Sistema Eléctrico Interconectado Nacional). The HRV mechanism combines the merchant and regulatory approaches to promote investment into transmission grids. This mechanism gives incentives for efficient investment in expansion of the network by the rebalancing over time of the fixed and variable charges of a two-part tariff in the framework of a wholesale electricity market with locational pricing. The expansion of the network is carried out through the sale of Financial Transmission Rights (FTR's) for the congested lines. The mechanism is applied for 103 nodes of the SEIN using detailed characteristics of generators, nodes and transmission lines. Under Laspeyres weights and linear cost of expansion of transmission capacity, it is shown that prices converge to lower levels as a result of increased transmission capacity.
Keywords: L51; L91; L94; Q40; 330; Electricity transmission expansion; incentive regulation; Peru; congestion management